Enhanced Wound Healing with Rhodiola rosea Phytosomal Gel: Extraction, Formulation, and In vivo Evaluation - Kalusalingam, Anandarajagopal; Khan, Abdullah; Kanakal, Mahibub Mahamadsa; Abbas, Syed Atif; Long, Chiau Ming; Bachi, Tazneem; Tan, Ching Siang; Bawazir, Abubakar Salam; Abdul Razak T.K.; Salfi, Roshan (Current Pharmaceutical Design, 2025)
BackgroundThis study explores the formulation and effectiveness of a Rhodiola rosea phytosomal gel for enhancing wound healing.ObjectiveThe ethanolic extract of Rhodiola rosea roots, rich in bioactive compounds like alkaloids and flavonoids, was optimized into a phytosomal complex to improve absorption and dermal retention.MethodsCharacterization through GC-MS revealed compounds, such as 2-Heptadecenal and Bicyclo[4.1.0]Heptane and 7-Pentyl. FTIR confirmed the successful encapsulation within the phospholipid bilayer, while SEM showed smooth, spherical particles.ResultsThe Box-Behnken design optimized formulation parameters, achieving high yield (92.64%), small particle size (355 nm), and high entrapment efficiency (93.98%). In vitro release studies displayed a consistent release profile, aligning with Zero-order and Hixson-Crowell models. In vivo evaluation on Wistar rats showed that the phytosomal gel significantly enhanced wound healing, achieving 98.16% wound reduction by day 14, compared to 95.17% for R. rosea extract and 97.13% for standard treatment. Histopathological analysis demonstrated complete tissue regeneration and well-organized collagen fibers in the phytosomal gel group.ConclusionThis research highlights the potential of Rhodiola rosea phytosomal gel as an effective wound healing therapy, with future studies suggested for extended stability tests and human skin permeation studies.
Keywords: Rhodiola rosea